Nitretação por plasma de hastes de ferro fundido para análise de desempenho em solos do semiárido - Martins, Amanda Dayane da Costa (Universidade Federal Rural do Semi-Árido, 2017)
This work consists in the application of DC and DC pulsed plasma processes in order to treat rods made of nodular cast iron, which is part of a equipment denominated scarifier, utilized in the land preparation in agriculture of potiguar semiarid. In the first step, it was researched the best nitriding condition and the best mechanical properties obtained in samples of sacrificial rods, in laboratory scale. Thus it was possible a comparative study with DC and DC pulsed power supply. Analysis techniques utilized for characterization of samples were: X-ray diffraction, microhardness measurements and Scaning Electron Microscopy (SEM). Microhardness measurements showed that samples nitrided presented significant increasing superficial hardness and longer time of treatment at work pressure of 2,5 mbar promoted the best results. In the second step, it was utilized the best condition of nitriding, in other words, a direct and optimized relation among temperature, pressure and time of treatment with layer thickness and superficial hardness in the treatment of work tools (rod of scarifier), posteriorly submitted to field tests. The results showed that the microhardness increasing influences the improvement of performance related to the weight loss by waste of the rods
Keywords: Plasma DC; Nitretação iônica; Escarificador; DC Plasma; Ionic nitriding; Scarifier; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA